ANALISIS ALOKASI DANA HIBAH DI PROPINSI BANTEN - Heni Rohaeni; Arenawati Arenawati (Universitas Sultan Ageng Tirtayasa, 2014)
Finance is important object in government . Finance managing is foundation to manage a country. Finance allocation must describe citizens need ,government need in public service and equity. Finance allocation can’t describe political interesting of the man who row the power. Grant fund is one item in budgeting. The Allocation of grant fund in Banten provience in 2013 is Rp. 415.451.525.000,00. It is 20,1 % from total budget in Banten provience. The proportion of Indirect funding is 39%, and 107 % of direct funding. This policy describe that funding for community development and infra strcture is less than grant fund. Fact, many organization which receiving grant fund is not accountabel and fictive, so if the alocation of grant fund too big its cause dis-oriented and manipulating in public budgeting.